HEPATOPROTECTIVE ACTIVITY OF OPUNTIA DILLENII (KER GAWL.) HAW. FRUIT PULP EXTRACT AGAINST CADMIUM INDUCED TOXICITY IN MICE - A. Shah; K. R. Ahmad; N. Aziz; S. Rahim; S. Batool; S. Suleman; T. Abbas; M. A. Kanwal (Journal of Animal and Plant Sciences, 2016)
The present study was conducted to evaluate the hepatoprotective activity of Opuntia dillenii (Ker Gawl.) Haw. (OD) fruit extract in mice (Mus musculus) against Cadmium (Cd) induced hepatic-histopathology. Thirty albino mice were randomly distributed in three groups (n=10). Control(C) (untreated group) maintained on regular supply of food and drinking water. The Cd and Cd+OD groups were given 50ppm Cd ions in drinking water for 15 days and Cd free water for the next 7 days. The Cd+OD group additionally received 0.2ml of OD fruit extract (once daily) by gavage on days 16-22. The histological slides in Cd group revealed scattered aggregations of hepatocytic debris in the wavy hepatic cords with little sinusoidal spaces in between. Mostly the hepatocytes were swollen containing enlarged nuclei and vacuolated cytoplasts. In Cd+OD group these pathological signs were partly reversed additionally scattered aggregations of hepatoblastic progenitor cells were also visible. Mean cross-sectional areas of central lobular vein, hepatocyte and hepatocytic nucleus were significantly (p≤0.05) higher in Cd (6368.34±5.87µ2, 400.9±20.01µ2 and 82.64±9.07µ2 respectively) than the control (3280.20±1.83µ2, 184.10±11.77µ2 and 65.86±7.1µ2) and Cd+OD (3824.64±2.17µ2, 389.51±26.74µ2 and 76.14±6.06µ2) groups whereas, the mean number of  hepatocytes per hepatic cord were significantly (p≤0.05) higher in control (11.60±.37) than Cd+OD (10.84±.43) and Cd (8.56±.32) groups; however the mean number of progenitor cells perunit area were significantly higher in Cd+OD (6.76±.26) than control (4.43±.23) and Cd (2.32±.21)group. These findings reflect the curative role of the O. dillenii fruit extract on the hepato- histopathological changes of Cd exposure in mice, clearly indicating its hepato-protective medicinal importance for similar possible human benefits.
Keywords: Opuntia dillenii; Cadmium toxicity; Hepatohistopathology; Mianwali